Full-face motorcycle helmet protection from facial impacts: an investigation using THOR dummy impacts and SIMon finite element head model. Issue 3 (3rd March 2016) - Whyte, Thomas; Gibson, Tom; Eager, David; Milthorpe, Bruce
Abstract : Objective: Facial impacts are both common and injurious for helmeted motorcyclists who crash; however, there is no facial impact requirement in major motorcycle helmet standards. This study examined the effect of full-face motorcycle helmet protection on brain injury risk in facial impacts using a test device with biofidelic head and neck motion. A preliminary investigation of energy absorbing foam in the helmet chin bar was carried out. Method: Flat-faced rigid pendulum impacts were performed on a THOR dummy in an unprotected (no helmet) and protected mode (two full-face helmet conditions). The head responses of the dummy were input into the simulated injury monitor finite element head model to analyse the risk of brain injury in these impacts. Results: Full-face helmet protection provides a significant reduction in brain injury risk in facial impacts at increasing impact speeds compared with an unprotected rider (p<0.05). The effect of low-density crushable foam added to the chin bar could not be distinguished from an unpadded chin bar impact. Conclusions: Despite the lack of an impact attenuation requirement for the face, full-face helmets do provide a reduction in head injury risk to the wearer in facial impacts. The specific helmet design factors that influence head injury risk in facial impacts need further investigation if improved protection for helmeted motorcyclists is to be achieved.